Pandangan Filsafat Pendidikan Islam Terhadap Manusia Dan Masyarakat - Dede Setiawan; M. Alwi AF; Fahmi Muhamad Aziz; Abdul Fajar; Yurna Yurna (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This article discusses the philosophical views of Islamic education regarding human beings and society. The main focus of this article is to explain the definition and purpose of Islamic education philosophy, the significant role of education in Islam, as well as the concepts of Islamic education and the relationship between human beings and society. The literature search method is used to gather relevant references from Indonesia. Using the methodology of literature search or literature review, this methodology involves searching and analyzing various relevant sources such as books, journal articles, and other publications related to the topic. In this article, the background and context of Islamic education are introduced as an educational system with strong spiritual and moral values. Islamic education aims to shape individuals who are faithful, pious, virtuous, and contribute positively to building a just and harmonious society. The principles of Islamic education, such as monotheism (Tawhid), natural disposition (Fitrah), noble character (Akhlak Mulia), knowledge and wisdom (Ilm and Hikmah), and social responsibility, are narratively explained to depict the Islamic perspective on human beings and society. Through this article, it is hoped that readers will comprehensively understand the philosophical views of Islamic education regarding human beings and society, as well as its relevance in building a just, harmonious, and socially just society.